Determination of The Suspect as A New Irrational Norm With The Paradigm of Presumption of Innocence - Sukardi Sukardi (STAI Miftahul Ula Nganjuk, 2024)
The terms suspect, defendant and convict are the legal statuses of a person who is undergoing the process of criminal justice in the criminal justice system, which is automatically provided by law and is not determined, accordingly, procedurally there are no regulations regarding its determination in the Criminal Procedure Code and its implementing regulations. The new paradigm that includes